Bahasa Inggris - Syahrul Riza; Mardhatillah; Dzikrul Rizki; Muhammad Aidi Noor Ihsan (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to evaluate the impact of the CTL model on cognitive and learning activities of fifth-grade students at SDN 16 Banda Aceh, particularly when their cognitive scores in heat transfer topics in science do not reach the minimum threshold (KKM) of 76. This quantitative research uses a one-shot case study design with measurement and observation sheets as instruments. The analysis shows that the average student score before using the CTL model was 80.76 with 72.73% classical completeness, and after using the CTL model, it was 76.33 with 69% classical completeness. Hypothesis testing indicated t count > t table (2.49 > 1.69), thus H1 is accepted. Average cognitive scores were C1 = 22, C2 = 27, and C3 = 31. The instructor's task average score was 4.74 (very good), and student learning experiences were 85% very good, 9% good, and 6% acceptable. The results indicate that the CTL model positively affects individual cognitive outcomes with an average score of 80.76. However, it does not significantly impact the percentage of classical completeness, which remained at 72.73%, below the required 80%. The CTL model enhances teacher and student learning experiences, making students more engaged and enthusiastic as the learning connects directly to their lives.